High‐yield production of recombinant CRM197, a non‐toxic mutant of diphtheria toxin, in the periplasm of Escherichia coli. Issue 7 (15th May 2017) - Goffin, Philippe; Dewerchin, Marianne; De Rop, Philippe; Blais, Normand; Dehottay, Philippe
Abstract: A high cell density fed‐batch process was developed for production of recombinant CRM197, a non‐toxic mutant of diphtheria toxin widely used as a carrier in polysaccharide‐protein conjugate vaccines. Fully soluble recombinant CRM197 was obtained in high yields and with an authentic N‐terminus, by targeting the protein to the periplasm of Escherichia coli using the Signal Recognition Particle (SRP)‐dependent signal sequence of FlgI. Response Surface Methodology (RSM) was used to optimize the set‐points of key process parameters (pH and feed rate at induction). Optimal production of periplasmic CRM197 was found at a slightly basic pH (7.5). The feed rate during induction was positively correlated with the accumulation of unprocessed cytoplasmic CRM197, consistent with limited capacity of the SRP secretion pathway. Decreasing the feed rate to align the protein synthesis rate with the secretion capacity, resulted in minimal production of cytoplasmic CRM197. Besides, the host background was found critical for production of periplasmic CRM197: B834(DE3) was the highest producer (>3 g/L), while BLR(DE3) produced one third less CRM197, and very low yields (290 mg/L) were obtained with HMS174(DE3). The optimized process is robust and linearly scalable, and represents a 20‐fold yield improvement compared to a process based on Corynebacterium diphtheriae . Abstract : Using co‐translational secretion, correctly folded soluble CRM197 can be obtained in high yields (> 3 g/L) in Escherichia coli. Optimization of bioprocess conditions further minimizes cytoplasmic accumulation of incorrectly folded ssFlgI‐CRM197 precursor by avoiding saturation of the SRP‐dependent secretion pathway.